Desenvolvimento, caracterização físico-química, antioxidante e perfil de compostos voláteis de bebidas fermentadas de jabuticaba (Myrciaria cauliflora SSP) - Santos, Viviane Aparecida Figueredo Oliveir (2015)
Due to the growing human health concern, every day, we discover new foods or products which have ability to fight free radicals, ie, inhibit and/or decrease the oxidative processes in the body. The transformation of the fruit and alcoholic beverage, ensure economic benefits, and also promotes an effective use of bioactive compounds. In this context, the aim of this study was to evaluate the effect of the type of pulping and strains of Saccharomyces cerevisiae on the quality of fermented jabuticaba drink, characterize chemically-physical, as well as bioactive and volatile compounds in fermented jabuticaba drinks. We prepared five fermented beverages jabuticaba inoculated with three different strains (coded TAQ, CAT and PMS), varying the pulping method (manual and mechanical). Panel test using the sort-preference test. The results showed no significant difference on fermented beverages jabuticaba as the pulping method. During the fermentation monitoring, we observed a very similar behavior in sugar consumption during fermentation. The physico-chemical analysis of fermented beverages jabuticaba showed that all drinks are prepared in accordance with Decree. 2314/1997, with an alcohol content 12-14 ºGL / 20 ° C. It is observed that the total acidity found in beverages are values between 175.33 to 200.67 meq / L, above the limit established by Brazilian legislation for table wine. As for the total sugar content found in fermented beverages jabuticaba, this ranged from 5.12 g / L and 5.88 g / L, which characterizes the drinks as "Medium dry," as Brazilian legislation for table wine (BRAZIL , 1988). The pH of the liquor was found in the range 3.5 to 3,6. Determinations of bioactive compounds were performed (polyphenols, tannins and anthocyanins), and phenolic compounds and flavonoids by spectrophotometry quantification of catechins and gallic acid, and organic acids by HPLC-DAD in fermented jabuticaba beverages; The highest levels of bioactive compounds and phenolic were found in the brew jabuticaba developed with PMS strain, with the highest content of total phenolics (431.7 mg gallic acid / L), polyphenols (10.18 GL 1) and total tannins and (3.38 g L-1); and the concentrations of flavonoids in fermented beverages jabuticaba ranged 12 from 93.1 mg of quercetin / L and 140.0 mg of quercetin / L. Jabuticaba fermented beverages prepared with mechanical pulping method and inoculated with the strains TAQ, CAT, and SMP, had the highest levels of gallic acid (91.8 mg / L, 70.3 mg / L and 58.8 mg / L, respectively). In brew samples of jabuticaba catechin was not identified. The main organic acids in fermented beverages identified and quantified jabuticaba were malic acid obtained a variation of 0.07667 mg / ml and 0.6871 mg / ml to respectively higher and lower concentrations; and tartaric acid varied from 0.0590 mg / ml and 0.1549 mg / ml. Completing the characterization of fermented beverages jabuticaba the profile of volatile compounds extracted by SPME was analyzed in GC / MS. Among the compounds identified highlighted 2-phenylethanol, 2-ethylhexanol, ethyl acetate, 10-epi-γ-eudesmol, α-eudesmol, γ-eudesmol, octanoic acid. The volatile fraction of terpenes was composed of forty-eight compounds in this class, some compounds found in fruit blemish as αeudesmol, 10-epi-γ-γ-eudesmol and eudesmol. These compounds may be used as fermented beverage jabuticaba markers, as are typical compounds of the fruit. Above given, the brew jabuticaba inoculated with PMS strain presented the best of volatile profile, and like other beverages prepared using mechanical pulping, had the highest concentrations of bioactive compounds.